Evaluation of critiques against Bohdan Chwedeńczuk’s semantic atheism - Remisiewicz, Łukasz (Hybris, 2018)
The article is diverse on two parts. In the first part, the author refers assumptions of Bohdan Chwedeńczuk book, “Przekonania religijne” [Religious Beliefs] that was devoted to justify the thesis according to which religious statements are meaningless. He emphasizes a role of so called Hume Requirement that was postulated as a demarcation line between meaningful and meaningless words in Chwedeńczuk argumentation chain. Next he indicates main objections against the Requirement which were considered by Chweden czuk. The second part of the article is a discussion with critiques that were emerging after publishing of “Przekonania”. Such philosophers as J. J. Jadacki, M. Przełęcki, K. Kondrat, M. Pawliszyn, W. Wolan czyk and I. Ziemin ski formulated a number of arguments against the thesis about meaninglessness of religious statements. Author shows that Jadacki, Przełęcki and Ziemin ski presented compelling arguments which cannot be undermine basing on the “Przekonania” text, thus these objections must be included if the Chweden czuk’s theory could be considered as justified. Arguments formulated by Kondrat and Wolan czyk are possible to refute and Pawliszyn’s critique is pointless.